Consequences of recombination for the evolution of the mating type locus in Chlamydomonas reinhardtii. Issue 3 (20th July 2019) - Hasan, Ahmed R.; Duggal, Jaspreet K.; Ness, Rob W.
Summary: Recombination suppression in sex chromosomes and mating type loci can lead to degeneration as a result of reduced selection efficacy and Muller's ratchet effects. However, genetic exchange in the form of noncrossover gene conversions may still take place within crossover‐suppressed regions. Recent work has found evidence that gene conversion may explain the low degrees of allelic differentiation in the dimorphic mating‐type locus ( MT ) of the isogamous alga Chlamydomonas reinhardtii . However, no one has tested whether gene conversion is sufficient to avoid the degeneration of functional sequence within MT . Here, we calculate degree of linkage disequilibrium (LD) across MT as a proxy for recombination rate and investigate its relationship to patterns of population genetic variation and the efficacy of selection in the region. We find that degree of LD predicts selection efficacy across MT, and that purifying selection is stronger in shared genes than in MT ‐limited genes to the point of being equivalent to that of autosomal genes. We argue that while crossover suppression is needed in the mating‐type loci of many isogamous systems, these loci are less likely to experience selection to differentiate further. Thus, recombination can act in these regions and prevent degeneration caused by Hill–Robertson effects.